In situ synchrotron investigation of degenerate graphite nodule evolution in ductile cast iron. (December 2021) - Wigger, T.; Andriollo, T.; Xu, C.; Clark, S.J.; Gong, Z.; Atwood, R.C.; Hattel, J.H.; Tiedje, N.S.; Lee, P.D.; Azeem, M.A.
Abstract: Ductile cast irons (DCIs) are of increasing importance in the renewable energy and transportation sectors. The distribution and morphology of the graphite nodules, in particular the formation of degenerate features during solidification, dictate the mechanical performance of DCIs. In situ high-speed synchrotron X-ray tomography was used to capture the evolution of graphite nodules during solidification of DCI, including degenerate features and the effect of the carbon concentration field. The degeneration of nodules is observed to increase with re-melting cycles, which is attributed to Mg-loss. The dendritic primary austenite and carbon concentration gradients in the surrounding liquid phase were found to control nodule morphology by locally restricting and promoting growth. A coupled diffusion-mechanical model was developed, confirming the experimentally informed hypothesis that protrusions form through liquation cracking of the austenite shell and subsequent localised growth. These results provide valuable insights into the solidification kinetics of cast irons, supporting the design of advanced alloys. Graphic abstract: Image, graphical abstract